Analisis Risiko Keamanan Pengunjung di Destinasi Wisata: Studi Kasus Terhadap Ancaman Kejahatan dan Strategi Mitigasinya di Wisata Alam Oasis - Nurliza Shamsudin, Alsya; Zulfikar Ali, Fikri; Putri Pamungkas, Risa; Paridah Muhtar, Siti (PT Alahyan Publisher Sukabumi, 2025)
This study aims to analyze visitors' perception of security and mitigation strategies implemented by managers in Oasis Nature Tourism tourist destinations. Using a mixed methods approach, data was collected through the distribution of questionnaires to 45 respondents and interviews with tour managers. Quantitative analysis was carried out with the help of SPSS version 25, including validity, reliability, and determination tests, while qualitative data were analyzed with the Miles & Huberman model. The results show that all safety perception indicators are valid and reliable, with Cronbach's Alpha value of 0.795. An R Square value of 0.691 indicates that 69.1% of visitors' decisions to come are influenced by their perception of on-site security. The findings of the interviews reinforce these results, where managers not only rely on formal systems, but build a sense of security through the active participation of all staff, a social approach to local residents, and cooperation with security forces. Security system evaluations are carried out periodically and adaptively. In conclusion, the perception of security is an important factor in attracting interest in visiting, and a community-based security approach can be an effective alternative in sustainable management of tourist destinations.